Optimasi Formula SNEDDS (Self-Nanoemulsifying Drug Delivery System) Ekstrak Daun Kejibeling Menggunakan Metode SLD (Simplex Lattice Design) - Mahiya Mahiya; Devi Ratnasari; Marsah Rahmawati Utami (Jurnal Ilmiah Wahana Pendidikan, 2022)
Kejibeling leaf as one part of the plant that is used as a natural medicine with various therapeutic effects. Plant extracts used as medicinal ingredients generally have poor solubility and result in low oral bioavailability. Kejibeling leaf extract is less soluble in water, so its pharmacologic effect is limited. Nanoemulsions can be an option for delivery systems which are expected to increase the solubility and bioavailability of oral administration. Nanoemulsifying formulation can be done through Self-Nanoemulsifying Drug Delivery System (SNEDDS). Simplex Lattice Design (SLD) is one of the optimization methods that can be used. This method is used to provide convenience in determining the optimal formula for the SNEDDS mixture. Testing on 14 formulas from Simplex Lattice Design resulted in the optimal formula for SNEDDS leaves of kejibeling with a composition of 2.22 (VCO): 54.23 (surfactant) : 43.55 (cosurfactant) with a transmittance value of 98.95% and an emulsification time of 47.12 seconds. Has a particle size of 11 nm with a PI value of 0.167 and a zeta potential value of -31.2 mV.